Smiling to Smiles After Exclusion: Social Rejection Enhances Affiliative Signalling - Philipp MC; Bernstein M; Vanman EJ; Johnston L (Massey University, 2014)
Reciprocating others' smiles is important for maintaining social connections as it both signals a common affective state to others and possibly induces empathetic reactions in the actor. Feelings of social exclusion may increase such "mimicry" as a means to improve affiliative bonds with others. Whether smile reciprocation differs based on the perceived smile type was the focus of this study. Young adults wrote about either a time they were excluded or a neutral event. They then viewed a series of smiles-half genuine and half posed. Facial electromyography recorded muscle activity involved in smiling. Excluded participants better distinguished the two smile types. They also showed greater zygomaticus (cheek) activity toward genuine smiles compared to posed smiled; non-excluded participants did not. The extent to which participants reciprocated the smiles was unrelated to their ability to distinguish between smile types. Affiliative motivation is discussed as a possible explanation for these effects.